Analysis of the Effect of Capacitor Bank Integration and Harmonic Filters on Improving Energy Efficiency and the Reliability of the Electrical System at Hotel Danau Toba Medan - Andri F M Siahaan; Zuraidah Tharo; Parlin Siagian (SEAN Institute, 2026)
Hotel Danau Toba Internasional Medan consumes a large amount of electricity due to the use of inductive and non-linear loads, which can reduce power quality. This study aims to evaluate the existing power quality and assess the effect of installing capacitor banks and harmonic filters in improving the efficiency and reliability of the electrical system. The methods used in this study include direct measurements, analysis referring to the IEEE Std. 519-2014 standard, and simulations with ETAP software version 16.0.0. The measurement results show a low power factor of 0.759, with a voltage drop reaching 15.65 kV from a nominal voltage of 20 kV, and the highest voltage unbalance recorded at 2.64% on panel 1 during the weekend. Based on the simulation results, the installation of a capacitor bank with a capacity of 525.22 kVAR can improve the power factor to 0.972 and reduce the current from 2015.2 A to 1782.6 A. To prevent resonance caused by harmonics, a reactor detuned by 8% is used. This implementation has been proven to increase energy efficiency, maintain system stability, and generate operational cost savings of IDR 221,400,000 annually.